Aflame : learning from silence - Iyer, Pico (Riverhead Books, 2025)
"From the bestselling author of The Art of Stillness, a revelatory exploration of the abiding clarity and calm to be found in quiet retreat. Pico Iyer has made more than 100 retreats over the past three decades to a small Benedictine hermitage, high above the sea in Big Sur, California. He's not a Christian-or a member of any religious group-but his life has been transformed by these periods of time spent in silence. That silence reminds him of what is essential and awakens a joy that nothing can efface. It's not just freedom from distraction and noise and rush: it's a reminder of some deeper truths he misplaced along the way. In Aflame, Iyer connects with inner stillness and joy in his many seasons at the monastery, even as his life is going through constant change: a house burns down, a parent dies, a daughter is diagnosed with cancer. He shares the revelations he experiences, alongside wisdom from other non-monastics who have learned from adversity and inwardness. And most profoundly, he shows how solitude can be a training in community and companionship. In so doing, he offers a unique outsider's view of monastic life-and of a group of selfless souls who have dedicated their days to ensuring there's a space for quiet and recollection that's open to us all. Radiant, intimate and gripping, Aflame offers ageless counsel about the power of silence, and what it can teach us about how to live, how to love and, ultimately, how to die"--